DAMPAK PENGGUNAAN POWERPOINT INTERAKTIF TERHADAP TINGKAT PERHATIAN, MOTIVASI DAN PEMAHAMAN KONSEP DI BIMBEL KAMPUNG SABI - Martha, Kurniawati; Siburian, Swyen Adven Tina; Gunanto, Yohanes Edi; Sitompul, Henni; Izaak, Maya Puspitasari (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2024)
In the era of globalization with rapid technological developments, technology is very useful in improving the efficiency and quality of learning. Not all students have the opportunity to learn how to use technology; one of them is the children in rented houses in Kampung Sabi, Tangerang. It is caused by the financial situation of parents who are unable to provide laptops, internet quotas, and cell phones. Based on the needs analysis, children in Sabi Village should have the opportunity to learn to utilize technology and then use interactive PowerPoint using the laptops of the Pelita Harapan University (UPH) team. The UPH team also downloads animations, images, videos and music, so they don't need an internet quota. As a result of the activity, using interactive PowerPoint can increase attention, motivation to learn, and understanding of science and mathematics concepts. The method of this activity is lecture, answering questions and brainstorming using interactive PowerPoint. This event will take place from 5 September 2023 to 30 May 2024. As a result, interactive PowerPoint has been proven to increase attention motivation to learn and make the material taught easier to understand. Children make learning activities interesting and fun. The benefit of using interactive PowerPoint is that 86.49% of children in Sabi Village are happier learning Mathematics and Science. This feeling of joy encourages children in Sabi Village to pay attention and be motivated to learn so they can understand the concepts being taught well.